2013
DOI: 10.1186/1471-2431-13-193
|View full text |Cite
|
Sign up to set email alerts
|

Development of an early nurse led intervention to treat children referred to secondary paediatric care with constipation with or without soiling

Abstract: BackgroundConstipation is a common chronic childhood condition referred to secondary care. Effective treatment requires early intervention, prolonged medication to soften stools and behavioural support to achieve a regular habit of sitting on the toilet to pass a stool. The purpose of this audit and service development was to assess routine consultant paediatrician-led care against minimum standards and if appropriate to develop a nurse-led intervention. The new care package could then be tried out within gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Conversely, interdisciplinary care models that can accommodate more frequent visits and as-needed contact with health care providers during symptomatic exacerbations or periods of uncertainty have shown promise. 42-45 Based on our concerning findings about the negative effects of misconceptions and parental frustration on family relationships and child outcomes, finding innovative ways to meets parents’ information and support needs is critically important to promote both parent and child well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, interdisciplinary care models that can accommodate more frequent visits and as-needed contact with health care providers during symptomatic exacerbations or periods of uncertainty have shown promise. 42-45 Based on our concerning findings about the negative effects of misconceptions and parental frustration on family relationships and child outcomes, finding innovative ways to meets parents’ information and support needs is critically important to promote both parent and child well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that these types of nurseled activity can improve the outcomes of children with asthma [31,32], as well as with other chronic conditions [33][34][35]. Those experts whose clinics employ nurses report that they are indispensable for helping patients manage their own asthma, for example by educating them on correct inhaler technique and avoiding exacerbating factors.…”
Section: Further Findingsmentioning
confidence: 99%
“…Characteristics of the included studies are provided in Tables 2 and 14 A total of 2252 children with constipation (range 15-1020 per study) were included in the 15 studies. [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] The age of children ranged between 1 month and 20 years. One study 62 included only children additional needs, and two studies explicitly excluded children with additional needs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The most frequently reported outcome of interest was faecal incontinence, reported by 10 studies. 58,60,61,63,[65][66][67][68]70,71 Only four studies assessed painful defaecation [59][60][61][62] and two assessed QoL. 65,67 No study assessed school attendance.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%